Reflectarray Resonant Element based on a Dielectric Resonator Antenna for 5G Applications - Sallehuddin, Nur Fazreen; Jamaluddin, Mohd Haizal; Kamarudin, Muhammad Ramlee; Dahri, Muhammad Hashim (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The performance of a proposed cross hybrid dielectric resonator antenna (DRA) element for dual polarization configuration operating at 26 GHz for 5G applications is presented in this paper. The new cross hybrid DRA unit cell is introduced which combines a cross shape DRA with a bottom loading cross microstrip patch. This technique of a bottom loading cross microstrip patch is chosen as the tuning mechanism (varying the length of the microstrip to tune the phase) instead of changing the DRA dimensions because of their ease of implementation and fabrication. By doing so, high reflection phase range with low reflection loss performance can be obtained, which is essential for a high bandwidth and high gain reflectarray for 5G applications. The design and simulation have been done using commercial software of CST MWS. The reflection loss, reflection phase and slope variation were analyzed and compared. A metallic cross microstrip patch of varying length placed beneath the DRA to act as the phase shifter to tune the phase and give smooth variation in slope with a large phase range. The proposed cross hybrid DRA unit cell provides a high reflection phase range of 342º and 1.8 dB reflection loss. The computed results are compared with experimental results revealing reasonable agreement, thereby confirming the viability of the design.